Meningitis mortality in Neurology Ward of Dr. Cipto Mangunkusumo hospital Jakarta (Medical Journal of Indonesia, 2006)
Mortality rate of meningitis is not decreased even though there is decreasing meningitis rate and advanced development of antibiotics. The purpose of this study is to find out meningitis mortality pattern and to evaluate factors related to meningitis mortality in hospitalized patients. Study was done using retrospective data from medical records of the patients administered in the Neurology ward of Cipto Mangunkusumo hospital from January 1997 — December 2005. Data were reported descriptively in texts and tables, and analyzed with Chi-square for categorical data and Student's "t" test for numerical data, then for final model using multinomial logistic regression analysis. Two hundred and seventy three patients were included in this study, consisted of 81 female patients and 192 male patients age between 12 to 78 years old. A hundred and fourteen patients died during and 159 patients lived. Decreased level of consciousness, especially stupor (OR 10.44, p 0.000) and coma (OR 53.333, p 0.000), and presence of motor weakness (OR 2.068, p 0.009) had relationship with outcome. Mortality rate of meningitis is still high (41.8%) because there are some factors that affect its prognosis. From this study, onset, level of consciousness, and motor weakness are predictors for meningitis death. (Med J Indones 2006; 15:236-41)